Effectiveness analysis of e-learning implementation models and resource support in higher education institutions: case studies and insights amidst the COVID-19 pandemic - Olena G. Glazunova; Maksym V. Mokriiev; Olena H. Kuzminska; Valentyna I. Korolchuk; Nataliia V. Morze; Liliia O. Varchenko-Trotsenko; Roman A. Zolotukha (Academy of Cognitive and Natural Sciences, 2023)
The COVID-19 pandemic has accentuated the need for comprehensive analysis of the effectiveness of e-learning implementation models and the supporting resources in higher education institutions. This article provides an overview of solutions and case studies, focusing on the selection and evaluation of individual services and learning management platforms. To gauge the effectiveness of electronic resources in meeting students' educational needs, the study recommends employing quantitative indicators in conjunction with students' performance descriptions. This includes leveraging educational analytics to gather data on students' frequency and duration of engagement with specific e-resources. The functionality modules "Course Comparison" of the Moodle Learning Management System (LMS) and "Statistics", along with the optional Analytics module, are reviewed. The article presents the results of applying these modules to analyze e-learning courses at the National University of Life and Environmental Sciences of Ukraine and Boris Grinchenko Kyiv University. Furthermore, the study investigates the factors contributing to students' limited usage of individual e-courses. By examining these case studies and shedding light on the reasons behind students' reduced engagement, this article contributes valuable insights to enhance the efficacy of e-learning implementation and resource support in higher education institutions.